Adsorption of Chromium (+3) from Aqueous Solutions using Adsorbent planting Mauve (malva parviflora) (Journal of the College of Basic Education, 2022)
In this research, There is the removal of (Cr+3) ions from aqueous solutions. By adsorption process on malva parviflora, It was attained to the equilibrium (60minute) which investigated by Atomic absorbtion spectrophotometer technique .The results show that the weight had better value (0.2 gm) . The effect of initial pH solution on adsorption had been studied in the range (3-10). The Freundlich and Langmuir equations were applied ,and the parameter of those equations had been calculated . The extent of adsorption was found to decrease as the temperature increased, i.e. exothermic process, and so the thermodynamic functions ΔH, ΔG and ΔS were calculated .